Stability of immediately loaded 3 mm long miniscrew implants: a feasibility study - Danielle GESHAY; Phillip CAMPBELL; Larry TADLOCK; Emet SCHNEIDERMAN; Hee-Moon KYUNG; Peter BUSCHANG (Dental Press Editora, 2021)
ABSTRACT Introduction: Shorter miniscrew implants (MSIs) are needed to make orthodontics more effective and efficient. Objective: To evaluate the stability, insertion torque, removal torque and pain associated with 3 mm long MSIs placed in humans by a novice clinician. Methods: 82 MSIs were placed in the buccal maxillae of 26 adults. Pairs of adjacent implants were immediately loaded with 100g. Subjects were recalled after 1, 3, 5, and 8 weeks to verify stability and complete questionnaires pertaining to MSI-related pain and discomfort. Results: The overall failure rate was 32.9%. The anterior and posterior MSIs failed 35.7% and 30.0% of the time, respectively. Excluding the 10 MSIs (12.2%) that were traumatically dislodged, the failure rates in the anterior and posterior sites were 30.1% and 15.2%, respectively; the overall primary failure rate was 23.6%. Failures were significantly (p= 0.010) greater (46.3% vs 19.5%) among the first 41 MSIs than the last 41 MSIs that were placed. Excluding the traumatically lost MSIs, the failures occurred on or before day 42. Subjects experienced very low pain (2.2% of maximum) and discomfort (5.5% of maximum) during the first week only. Conclusions: Shorter 3 mm MSIs placed by a novice operator are highly likely to fail. However, failure rates can be substantially decreased over time with the placement of more MSIs. Pain and discomfort experienced after placing 3 mm MSIs is minimal and temporary.